The diagnostic and prognostic value of serum miR-199a-5p combined with echocardiography in acute myocardial infarction - Lixin Xu; Jianfeng Lin; Jianke Xia; Deng Chen; Guohan He (Journal of Cardiothoracic Surgery)
Abstract Background Diagnosis and prognostic evaluation of acute myocardial infarction (AMI) are crucial for patients. Objective The clinical significance of serum miR-199a-5p combined with echocardiography in AMI was investigated to provide some reference for clinical treatment. Methods The study subjects were 90 AMI patients and 50 acute chest pain patients (control). All patients were examined by echocardiography and recorded LVEDV, LVESV, and LVEF. RT-qPCR was performed to detect the serum miR-199a-5p level. Pearson analysis was used to analyze the correlation of miR-199a-5p with LVEF and cTnI. The diagnostic value of miR-199a-5p combined with LVEDV, LVESV, and LVEF was assessed by the ROC curve. The occurrence of major adverse cardiovascular events (MACE) was recorded to analyze the prognostic value of miR-199a-5p by the Kaplan-Meier curve and Cox regression. Results Serum miR-199a-5p was elevated in AMI, positively correlated with cTnI and negatively correlated with LVEF. The combination of miR-199a-5p with LVEDV, LVESV, and LVEF enhanced the sensitivity and specificity for the diagnosis of AMI. Patients with high miR-199a-5p expression were more likely to develop MACE. The combination of miR-199a-5p with LVEF improved the prediction of MACE. Conclusions The combination of miR-199a-5p with echocardiography improved the diagnostic efficiency of AMI and provided prognostic information.